MEDIA DAN POLITIK: STUDI KASUS KONSTRUKSI CITRA POLITIK JOKOWI-MA’RUF DAN PRABOWO-SANDIAGA DI KORAN JAWA POS DALAM PEMILU 2019 - Nia Silviana; Ucu Martanto (Universitas Airlangga, 2020)
This study examines the correlation between reporting by the mass media and the marketing strategies desired by each success team in the 2019 Presidential Election. To find this out, the author uses discourse analysis from Fairclough, because this method is able to show the integration between a) text analysis, b) analysis of the production process, consumption and distribution of texts, and c) sociocultural analysis. There is no significant difference related to the reporting of Jokowi-Ma’ruf and Prabowo-Sandiaga in the Jawa Pos newspaper, both in qualitative and quantitative terms. Although there are similarities between the political image built by actors and the image constructed by the media, it does not mean that it is based on political cooperation. The selected setting and framing agenda is based on consideration of the selling value of information for the reader. This shows that the mass media as well as the opinion of Croteau and Hoynes (2001) in Stromback (2011) are considered to be oriented towards commercial businesses on how to serve the wants and needs of the audience and advertisers. However, the media and actors are mutually beneficial in this regard, because political reporting is a commodity sought by readers, while political actors need the media to deliver their political products to the public.